Tracing Lack: Lacan, the Letter and The Origin of the World - Molina Barea, María del Carmen (2022)
The present paper provides creative insight into Jacques Lacan’s theoretical understanding of sexual difference from an unconventional perspective, in the attempt to develop a critical approach as well as a concrete alternative to the Lacanian declaration the woman does not exist. To this end, this paper revisits the notion of unconscious desire, methodologically inspired by Gilles Deleuze and Felix Guattari and Luce Irigaray. In this line, it will also redefine the power of the letter as trace’s enjoyment, thus subverting the potential of Chinese and Japanese calligraphy analyzed by Lacan. With this aim, certain cases studies will be of use, such as the Taoist painter Shitao, the semiographies painted by André Masson, and The Origin of the World, the painting by Gustave Courbet which was owned by Lacan himself. The crucial aspect is ultimately to locate lack as the essential product of castration within the symbolic signifier -also knowned as Phallus and the Name of the Father- which rules the Other’s production of subjectivity, excluding women from language and representation.